Assessment of safety and adverse drug reactions of COVID vaccination in the South Indian population: An observational prospective cross-sectional study. (December 2022) - Manda, Anusha; Koya, Pranathiya; Pallem, Ravali; Mohd, Danish; Thatikonda, Keerthi; Venkateshwarlu, K.
Abstract: Background: COVID vaccination is now offering a way to transit out of this phase of the pandemic. Two vaccines were approved by the Central Drugs Standard Control Organization (CDSCO) in India: Covishield and Covaxin. However, the vaccines are known to have Adverse Drug Reactions (ADRs) like fever, body pains, headache, pain, and swelling at the injection site. Aim: To assess the Safety of ADRs with Covid Vaccination in the South Indian Population. Method: This prospective, multi-centric study was carried out for six months (February 2021–July 2021). Subjects vaccinated against COVID were enrolled in the study. Informed consent was taken from the study participants, and required data (age, gender, type of vaccine, and ADRs) was collected through telephonic interviews. The data were analyzed by using the Chi-square test. Results: A total of 3032 participants were enrolled in the study. The prevalence of ADRs is highly observed after the 2nd dose (51%) of COVID vaccination. ADRs were mainly experienced by females (55%) than males (45%). The incidence of fever and body pains was high in Covishield after dose one and Covaxin after dose 2. The pain at the injection site was high in Covaxin after dose 2. The WHO assessment scale and Naranjo's scale shows that ADRs are higher likely than probable. Conclusion: We concluded that frequent ADRs that occurred with Covaxin and Covishield were fever, body pains, weakness, headache, and pain at the injection site. All the ADRs were mild and manageable with Paracetamol. So, the vaccines are safe to administer. Highlights: Due to the rapid development of covid-19 vaccines, there is hesitancy among communities to take them. This study assesses the ADRs that occur with Covaxin and Covishield. Our study shows different ADRs caused by the Covid vaccination and their percentage incidence. It also represents the severity of ADRs of Covid vaccination according to age, gender, and type of vaccine. This study reported no severe or significant ADRs associated with covid-19 vaccines.